Sámi Early Childhood Education and Sustainability in the Arctic - Laiti, Marikaisa; Määttä, Kaarina; Köngäs, Mirja Johanna (İsmail şahin, necmettin erbakan üniversitesi eğitim fakültesi bilgisayar ve eğitim teknolojileri bölümü meram, 2024)
The Sámi are indigenous people living in Finland, Norway, Sweden, and Russia. There are about 10,500 Sámi in Finland. The traditional settlement area of the Sámi is located in the Arctic. Endangered Inari, Skolt, and Northern Sámi languages are spoken in Finland, and efforts are made to implement the traditions, principles, and values of indigenous culture. The traditional settlement area of the indigenous Sámi people is in the Arctic. The Sámi culture and languages are in a vulnerable position due to their present climate change. Early childhood education (ECE) is of particular value to contribute to the preservation and strengthening of indigenous culture and, consequently, to sustainable development in the Arctic. The purpose of this article is to describe Arctic sustainable Sámi early childhood education based on the perceptions and experiences of Sámi early childhood educators in Finland. The research shows that cultural sustainability was approached by using Sámi language in activities, supporting children’s Sámi identity, using materials and items important in culture, and having a tight connection with Sámi community. Peer reviewed